Theoretical approach of macroeconomic policy measures for solving economic consequences of Covid-19 - Elizabeta Djambaska; Aleksandra Lozanoska (Institute of Economics – Skopje, 2020)
COVID-19 is a virus that cause health problems to the population and spread very fast in the world as a pandemic. At the same time when the health and human lives are affected, economy is also impacted by an outbreak. The primary effect of the corona crisis, that defers it from some previous ones, is that the initial economic shocks occur simultaneously on supply and demand side. The shocks initially are caused by the state measures taken for the virus spreading i.e. the state decree for restrict or prohibit human movement, tourist travel, the work of business entities in some activities was completely reduced, in others significantly limited. Hence, one of the first sectors impacted by an outbreak is the public and private health system, then tourism, trade, transport, agriculture, constructions and industry. Indirectly and in very short time the functioning of the whole economy is threatened. The main question is, are the government interventions in the economy necessary and which measures are appropriate to manage the economic consequences from the pandemic. This paper discusses about the theoretical approach of the macroeconomic measures that government can use on both supply and demand side in the economy, for solving the imbalance. Important part of the paper is the short review of some ongoing macroeconomic policy measures in the EU countries and in North Macedonia, as an active response to the pandemic effects.
Keywords: pandemic, economic shocks, macroeconomic imbalances, state interventions, monetary and fiscal measurements